2000
DOI: 10.1115/1.429661
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte Translocation Response to Direct Current Electric Fields

Abstract: Using a custom galvanotaxis chamber and time-lapse digital video microscopy, we report the novel observation that cultured chondrocytes exhibit cathodal migration when subjected to applied direct current (DC) electric fields as low as 0.8 V/cm. The response was dose-dependent for field strengths greater than 4 V/cm. Cell migration appeared to be an active process with extension of cytoplasmic processes in the direction of movement. In some cells, field application for greater than an hour induced elongation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 61 publications
7
91
0
1
Order By: Relevance
“…Direct current at constant EF strength (0-6 V cm -1 for sparse cells, 0-2 V cm -1 for monolayers, 37°C) was applied to galvanotaxis chambers (Chao et al, 2000) connected to a power supply (Keithley SourceMeter 2410) through two salt bridges and Ag-AgCl electrodes. Time-lapse images (10 minute intervals) were captured and the average speed (the distance between the final and initial positions of the cell centroid divided by the total elapsed time) was analysed using a particle-tracking scheme in MetaMorph software (Universal Imaging).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct current at constant EF strength (0-6 V cm -1 for sparse cells, 0-2 V cm -1 for monolayers, 37°C) was applied to galvanotaxis chambers (Chao et al, 2000) connected to a power supply (Keithley SourceMeter 2410) through two salt bridges and Ag-AgCl electrodes. Time-lapse images (10 minute intervals) were captured and the average speed (the distance between the final and initial positions of the cell centroid divided by the total elapsed time) was analysed using a particle-tracking scheme in MetaMorph software (Universal Imaging).…”
Section: Methodsmentioning
confidence: 99%
“…Galvanotaxis and galvanotropism (i.e. EF-mediated migration and shape change, respectively) occur in keratinocytes, epithelial cells, bone cells, chondrocytes and fibroblasts (Chao et al, 2000;Ferrier et al, 1986;Sheridan et al, 1996;Soong et al, 1990;Zhao et al, 1996a). The EF strengths commonly used (1-10 V cm -1 ) are physiologically significant for vertebrates, because 1-2 V cm -1 gradients have been measured on either side of the cut surface of wounds owing to ion flux through leaky cell membranes (Soong et al, 1990) or transepithelial potential driven by Na + pumps (Vanable, 1989).…”
Section: Cdc42 and Its Downstream Effectorsmentioning
confidence: 99%
“…In the present study, we investigated the migratory response of fibroblasts derived from the ACL to an EF (E = 0-6V/cm, [31]), applied in a static or pulsing manner. The ACL is an intra-articular ligament that is often torn in sports-related injuries and is critical in stabilization of the knee joint [29,32].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in LNCaP cells and fish keratocytes, thapsigargin, which depletes internal Ca 2+ stores, blocks the response to dcEFs (Perrett et al, 1999;Brust-Mascher and Webb, 1998 (Berridge, 1993;Dawson, 1997). Neomycin, an antagonist of phosphoinositide signalling, inhibits the response of chondrocytes to dcEFs (Chao et al, 2000). Similar experiments on embryonic muscle cells showed that galvanotaxis is not restored even in the presence of a 16-fold increase in the level of extracellular Ca 2+ (McCaig and Dover, 1991).…”
Section: Influx Through Voltage-gated Ca 2+ Channelsmentioning
confidence: 99%